"Asians for Black Lives, Not Asians for Asians": Building Southeast Asian American and Black Solidarity. (15th September 2020) - Lee, Stacey J.; Xiong, Choua P.; Pheng, Linda M.; Neng Vang, Mai
Abstract : This paper explores the possibilities and challenges of building cross‐racial solidarity between Southeast Asian American and Black communities through an ethnographic account of a community‐based educational space (CBES) working with low‐income Southeast Asian American and Black youth. CBESs can play a unique role in teaching youth to engage in anti‐racist work and building cross‐racial coalitions. We argue that attention to challenging anti‐Blackness is central to cross‐racial coalitions but should also recognize the distinct nature of anti‐Asian racism.